La costumbre como proceso creador del derecho internacional penal: ¿legitimidad o adecuación forzada? - Muracciole Goldberg, Maura Jazmín (2021)
This paper analyses the role of international custom as a source of International Criminal Law. It specifically seeks to determine its legitimacy in this field, focusing on the judgements of the International Criminal Tribunal for the former Yugoslavia, based on the principle of legality. It provides examples through different emblematic cases such as Tadic, Erdemovic and Dedalic. This paper holds the hypothesis of international custom being a legitimate creative process of law, according to the principle of legality in International Criminal Law. In this regard, a brief introduction considers the issue of international custom in this legal area, along with a short historical review. It then deals with the main criticisms to the use of the custom. Among them, we find the absence of written records, the difficulty in determining its moment of creation, or it is being considered contrary to the human rights principles. Thirdly, it carries out an analysis of the principle of legality, which is to serve as a parameter of legitimacy. The definition of the principle of legality would contribute to the analysis of the legitimacy of the custom. Lastly, it comments on the alternatives to consider international custom as a legitimate creative process. This paper ends with a set of personal reflections that propose reconsidering the sources of International Criminal Law